(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In this article, the emergence of a comic, socially critical trend of domestic life in the landscape genre with social content, emotional elegance, psychological subtlety and sharp life observations, and the domestic genre in painting and its current issues are discussed in detail.